Analisis BOD pada Limbah Industri: Perbandingan Kualitas Air di Inlet dan Outlet IPAL - Putwi Ayu Faradila; Budhi Oktavia (MASALIQ, 2025)
This study is motivated by the issue of declining water quality due to increasing demand that is not matched by optimal waste management. The objective of the research is to determine the Biochemical Oxygen Demand (BOD) levels in industrial wastewater by comparing the BOD concentrations at the inlet and outlet points of a wastewater treatment system. A quantitative approach was employed, using two samples obtained through purposive sampling. Data were collected through field observation and analyzed descriptively and quantitatively. The results show a decrease in BOD levels from 3.99 mg/L at the inlet to 3.41 mg/L at the outlet, indicating that the treatment process effectively improves wastewater quality. The main conclusion of the study is that lower BOD levels in a body of water reflect higher oxygen availability, resulting in better water quality that poses less risk to aquatic life and human users. The implications of this research contribute to the existing literature on industrial wastewater BOD analysis and offer recommendations for industries and policymakers to enhance the effectiveness of wastewater treatment systems and implement ongoing water quality monitoring policies. The study also opens opportunities for further research on innovative wastewater treatment technologies and analysis of other water quality parameters such as COD, TSS, and heavy metals.